Influence of the shape, thermal radiation, and variable properties on the turbulent buoyancy-driven airflow inside cavities with Trombe wall geometry. (4th March 2018) - Zamora, B.; Kaiser, A. S.
ABSTRACT: The effects of the radiative heat transfer and the influence of air variable properties on the natural convection flows in cavities with Trombe wall geometry are numerically investigated. The influence of considering surface-radiative effects on the differences reached for the Nusselt number and the mass flow rate obtained with several heating intensities is studied. The effects of the shape change consisting of varying slope angle of the heated wall is also analyzed. The influence of the thermal radiation on the appearance of the burnout phenomenon becomes particularly relevant. Important changes in the thermal and dynamic flow patterns are observed for high enough values of the wall slope angle.